2007
DOI: 10.1002/pen.20953
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial ratchetting behavior of vulcanized natural rubber

Abstract: Most of rubber engineering components endure cyclic loading during their service, and a nonzero mean stress during cyclic loading may cause an accumulation of strain which is known as ratchetting phenomenon. In order to study the ratcheting effect of rubber, a series of uniaxial ratchetting experiments were conducted on vulcanized natural rubber (NR). The effects of cyclic stress amplitude, mean stress and their histories on ratchetting behavior were studied, respectively. The uniaxial ratchetting behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
2
14
2
Order By: Relevance
“…3, it is seen that: (1) apparent ratcheting occurs during the cyclic tests of both the PC-7030PJ and PC-7020PJ polymers. The ratcheting strain increases with the number of cycles in the direction of tensile mean stress, while the ratcheting strain rate decreases rapidly in the first beginning of cyclic loading and a stable ratcheting with a constant ratcheting strain rate is reached after certain cycles, which is similar to that observed in the cyclic tests of other polymer materials [13][14][15][16][17][18].…”
Section: Effects Of Stress Levelssupporting
confidence: 80%
See 1 more Smart Citation
“…3, it is seen that: (1) apparent ratcheting occurs during the cyclic tests of both the PC-7030PJ and PC-7020PJ polymers. The ratcheting strain increases with the number of cycles in the direction of tensile mean stress, while the ratcheting strain rate decreases rapidly in the first beginning of cyclic loading and a stable ratcheting with a constant ratcheting strain rate is reached after certain cycles, which is similar to that observed in the cyclic tests of other polymer materials [13][14][15][16][17][18].…”
Section: Effects Of Stress Levelssupporting
confidence: 80%
“…Shariati et al [15] experimentally investigated the uniaxial ratcheting and fatigue failure of polyacetal polymer. Yu et al [16,17] observed the uniaxial and multiaxial ratcheting behaviors of vulcanized natural rubber. Pan et al [18] demonstrated that the ratcheting deformation of polyetherimide polymer would occur both before and after the apparent yield, which is different from that of metal materials discussed in [3,5,8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The smaller the v is, the more brittle the BMGs become. This correlation was verified in various BMGs with markedly different plasticity [20][21][22]. The mass densities q and the elastic moduli at room temperature for Mg 65 Cu 25 Y 10Àx Gd x system are shown in Table 1 Fig.…”
Section: Resultssupporting
confidence: 53%
“…For example, Chen et al investigated the uniaxial ratcheting behavior of PTFE under cyclic compression and constructed a simple constitutive model with stress rate effects (Chen and Hui, 2005;Zhang et al, 2008). Other polymer materials have also been investigated by various authors (Yu et al, 2008;Wang et al, 2010;Shariati et al, 2012;Avanzini, 2008;Liu et al, 2008;Li et al, 2013;Xu et al, 2014). The effect of thermal cycling aging on materials and structures has been adequately documented to improve the stability and reliability of the components Pang et al, 2001;Chiu et al, 2002;Jang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%